2022
DOI: 10.3389/fcvm.2022.843602
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Apolipoprotein(a) Phenotype Rather Than Lipoprotein(a) Is Associated With Coronary Atherosclerosis and Myocardial Infarction

Abstract: Background and AimsCurrent evidence suggests that lipoprotein(a) [Lp(a)] level above 50 mg/dL is associated with increased cardiovascular risk. Our study aim was to determine the relationship of apolipoprotein(a) [apo(a)] phenotypes and Lp(a) concentration below and above 50 mg/dL with coronary atherosclerosis severity and myocardial infarction (MI).Material and MethodsThe study population consisted of 540 patients (mean age 54.0 ± 8.8 years, 82% men) who passed through coronary angiography. The number of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…This is mainly due to the variations in the method for determining Lp(a), the difference in the methods used for phenotyping apo(a), and the patient groups. We have previously shown that the low-molecular-weight (LMW) apo(a) phenotype is associated with severe coronary atherosclerosis and myocardial infarction (MI) in patients with Lp(a) levels above 50 mg/dL, especially in those younger than 50 years [ 3 ]. The significance of LMW apo(a) as a risk factor for MI could not be determined retrospectively.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the variations in the method for determining Lp(a), the difference in the methods used for phenotyping apo(a), and the patient groups. We have previously shown that the low-molecular-weight (LMW) apo(a) phenotype is associated with severe coronary atherosclerosis and myocardial infarction (MI) in patients with Lp(a) levels above 50 mg/dL, especially in those younger than 50 years [ 3 ]. The significance of LMW apo(a) as a risk factor for MI could not be determined retrospectively.…”
Section: Introductionmentioning
confidence: 99%